(untitled) (Journal of Parents and Teachers, 2014)
This article talks about Américo Monteiro de Aguilar, a Portuguese teacher of the 20th century who did not turn his back on social problems. It can be seen how education was his true vocation; his educational conception was within the framework of Christian humanism. He opened Homes for abandoned youth and carried out multiple socio- educational actions with poor children to fight illiteracy and poor school attendance; he was always inspired by social and Christian principles. It is worth mentioning the Homes he opened in several Portuguese cities with the aim of offering a decent standard of living to young people who turned 18, and thus remove them from the crime and delinquency of the streets.